The Effect Of Investment Opportunity Set And Profitability On Stock Prices With Dividend Yield As Mediator - Hulu, Nuril Insyirah; Adib, Noval (Telaah Ilmiah Akuntansi dan Perpajakan, 2025)
This study aims to provide empirical evidence regarding the effect of the investment opportunity set (IOS) and profitability on stock price in publicly listed companies on the Indonesia Stock Exchange, with dividend yield as a mediating variable. This quantitative study uses secondary data from financial statements of companies listed on the Indonesia Stock Exchange (IDX), selected using a purposive sampling technique. The analysis results using Structural Equation Modeling - Partial Least Squares (SEM-PLS) show that IOS and profitability positively affect dividend yield but have no significant direct effect on stock price. Dividend yield mediates the relationship between IOS, profitability, and stock price in publicly listed companies on the Indonesia Stock Exchange. These findings align with Signaling Theory, which posits that dividend yield serves as a positive signal to investors, and are also supported by Bird in Hand Theory, which states that investors prefer certain dividends over future capital gains. This study contributes empirical evidence to the development of investment theory, particularly regarding internal company factors that influence stock price in the Indonesian capital market.